Resistance to Mecillinam and Nine Other Antibiotics for Oral Use in Escherichia coli Isolated from Urine Specimens of Primary Care Patients in Germany, 2019/20 - Michael Kresken; Yvonne Pfeifer; Florian Wagenlehner; Guido Werner; Esther Wohlfarth; on behalf of Study Group 'Antimicrobial Resistance' of the Paul Ehrlich Society for Infection Therapy (MDPI AG, 2022)
Urinary tract infections (UTIs) are among the most common bacterial infections in humans. Escherichia coli is by far the leading cause of community-acquired UTIs. Pivmecillinam, the oral prodrug of the penicillin derivative mecillinam (amdinocillin), was re-introduced in Germany in March 2016 for first-line treatment of acute uncomplicated cystitis. This study aimed to evaluate the prevalence of resistance to mecillinam in comparison to nine other antibiotics used for oral treatment in E. coli urine isolates after the re-introduction of pivmecillinam. A total of 460 isolates were collected at 23 laboratories of clinical microbiology between October 2019 and March 2020. Forty-six isolates (10.0%) produced an extended-spectrum β-lactamase (ESBL) of the CTX-M family. Resistance to amoxicillin (43.3%) was most widespread, followed by resistance to trimethoprim-sulfamethoxazole (27.0%), amoxicillin-clavulanic acid (18.0%), cefuroxime (11.3%), and ciprofloxacin (11.1%). Twenty-four E. coli isolates (5.2%) were resistant to mecillinam. The concentrations of mecillinam needed to inhibit 50/90% of the ESBL-producing isolates and the remaining isolates were 1/4 mg/L and 0.5/4 mg/L, respectively. The findings support the recommendation to regard pivmecillinam as a first-line option for the treatment of uncomplicated lower UTIs.